Potential of transforming sodalite from synthesis kaolin with a mild condition of the hydrothermal method - Sazali, Norsuhailizah; Harun, Zawati; Abdullahi, Tijjani; Azhar, Faiz Hafeez; Ahmad, Azlinnorazia; Rasli, Nurul Izwanie; Sazali, Norazlianie (AMG Transcend Association, 2022)
The hydrothermal synthesis method is one of the successful methods for transforming kaolin into sodalite with various parameters considered. The variation of alkalinity source of 2-3 Molarity of sodium hydroxide and crystallization time (12-16 hours) was considered an important parameter that influences the formation of sodalite. It is reported in this research that the process of synthesizing sodalite to transform into an amorphous stage (Metakaolinization phase) began with beneficiation of kaolin to remove the impurities and calcination by 6500C for four hours. The synthesis was done through an aging process (400C, 24 hours), and the crystallization temperature was 1000C. The kaolin was characterized by XRD, FESEM, FTIR, PSA, TGA, followed with metakaolin by XRD, FESEM, FTIR, and the end-product by XRD, FESEM, FTIR, and PSA. The crystallinity percentage of sodalite slightly increased by increasing the molarity and crystallization time, but quartz remains in the end-product.